K2SrP4O12: a deep-UV transparent cyclophosphate as a nonlinear optical crystal. Issue 58 (2nd July 2019) - Bai, Zhiyong; Liu, Lehui; Zhang, Lizhen; Huang, Yisheng; Yuan, Feifei; Lin, Zhoubin
Abstract : First cyclotetraphosphate as a nonlinear optical crystal with moderate second-generation harmonic response and short absorption edge. Abstract : Benefiting from high transmittance of PO4 tetrahedra in the deep-ultraviolet (deep-UV) region, phosphates have been investigated as deep-UV nonlinear optical (NLO) candidates for years. So far, reported deep-UV NLO phosphates are orthophosphates and polyphosphates while cyclophosphates, important members of the phosphates family, have usually been neglected for use as deep-UV NLO crystals. Here, we first report a novel cyclotetraphosphate K2 SrP4 O12 (KSPO) as a deep-UV transparent NLO crystal. In its structure, the fundamental building groups are ring [P4 O12 ] 4− groups. KSPO exhibits a moderate second-harmonic generation (SHG) response that is 0.5 times that of KH2 PO4 (KDP) and a short deep-ultraviolet absorption edge smaller than 200 nm.